Implications of AI Technology on Higher Level Education Development in Batam - Eryc Eryc; William Nurdin Wijaya; Indasari Deu (Universitas Islam Kuantan Singingi, 2025)
This study examined artificial intelligence impact on higher education in Batam, focusing on its potential to improve teaching, learning, and administration while addressing concerns such as reduced human interaction and ethical dilemmas. The research aimed to provide insights into the effective integration of AI to enhance educational outcomes and promote innovation in Batam. Data from 331 college students in Batam were collected using Cluster Disproportional Random Sampling and analyzed through PLS-SEM, examining seven variables. Perceived Risk did not significantly impact Attitude, as students perceived AI uncertainty but remained unaffected, while Facilitating Conditions weakly influenced Behavioural Intention, likely due to students prioritizing other factors and having independent access to AI via personal devices. AI's impact on education showed that factors such as resources, ease of use, and performance shaped students perspective, although the study's limitations include a small sample size in each university and a lack of demographic diversity